2019
DOI: 10.1093/mnras/stz2328
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the Small Magellanic Cloud using multiwavelength photometry of classical Cepheids

Abstract: This is the second of a series related to the study of geometry of the Magellanic Clouds based on multi-wavelength photometry of classical Cepheids. In this paper we determine the geometrical and viewing angle parameters of the Small Magellanic Cloud (SMC) using the Leavitt law for classical Cepheids with/without a break in the law at a certain period as reported in the literature. The study utilises photometric data for more than 3400 common classical Cepheids (Fundamental (FU) and First overtone (FO)) in opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The geometry of the SMC is complex, with a substantial line-of-sight depth. The northeastern regions of the dwarf appear to lie closer to us than its western edge, as perceived through numerous stellar tracers, including star clusters, red clump stars, Cepheid Variables, and RRL (see, e.g., Crowl et al 2001;Haschke et al 2012;Subramanian & Subramaniam 2012;Deb et al 2015Deb et al , 2019Scowcroft et al 2016;Muraveva et al 2018). The SMC red clump Figure 14.…”
Section: Smc Shape and Disruptionmentioning
confidence: 99%
“…The geometry of the SMC is complex, with a substantial line-of-sight depth. The northeastern regions of the dwarf appear to lie closer to us than its western edge, as perceived through numerous stellar tracers, including star clusters, red clump stars, Cepheid Variables, and RRL (see, e.g., Crowl et al 2001;Haschke et al 2012;Subramanian & Subramaniam 2012;Deb et al 2015Deb et al , 2019Scowcroft et al 2016;Muraveva et al 2018). The SMC red clump Figure 14.…”
Section: Smc Shape and Disruptionmentioning
confidence: 99%
“…From a number of studies has emerged a picture of the stellar component of the SMC as an elongated, cigar-like structure, often modeled as a triaxial ellipsoid highly inclined to the plane of the sky (e.g. Subramanian & Subramaniam 2012;Jacyszyn-Dobrzeniecka et al 2016;Deb et al 2019), with the North-East portion closer to us than the central and South-West portions. Fig.…”
Section: Distance Determination From Analysis Of Trendsmentioning
confidence: 99%
“…Since then there have been numerous studies of the SMC structure and geometry (e.g. Subramanian and Subramaniam 2009, Subramanian and Subramaniam 2012, Subramanian and Subramaniam 2015, Ripepi et al 2017, Deb et al 2019. Subramanian and Subramaniam [2009] confirmed the large line of sight depth in the outer regions of the SMC, using a similar method as in Hatzidimitriou and Hawkins [1989].…”
Section: Three Dimensional Structure Of the Smcmentioning
confidence: 83%
“…More recently, Deb et al [2019] using classical Cepheids and modeling the observed 3D distribution as a trixial ellipsoid obtained the geometrical and viewing parameters of the SMC. More specifically, the viewing angle parameter have inclination angle i= 3.465 • ± 0.030 • with respect to longest axis from the line of sight and position angle of line of major axis is θ=63.086 • ± 0.117 • .…”
Section: Three Dimensional Structure Of the Smcmentioning
confidence: 99%